Case report: Reconstruction of the long-gap unilateral absence of right pulmonary artery with contralateral pulmonary artery flap and autologous pericardial graft - Li, Tiange; Ling, Yunfei; Xiong, Ziqing; An, Qi (Frontiers in Cardiovascular Medicine, 2023)
Unilateral absence of pulmonary artery (UAPA) is a rare type of congenital abnormality that may coexist with other congenital abnormalities or present as an isolated lesion, the latter form can be asymptomatic. Surgical procedure is usually carried out when UAPA was diagnosed with significant symptoms, and the aim of surgery is to restore the pulmonary flow distribution. The right-side UAPA is a considerable challenge for surgeons to process surgery, however, technical description of this type of UAPA are limited. Here we described a rare case of a two-month girl with absence of right pulmonary artery, we presented a technique that reconstructs this long-gap UAPA with contralateral pulmonary artery flap and autologous pericardial graft.